Use of Emergency Departments among Working Age Adults with Disabilities: A Problem of Access and Service Needs. (26th December 2012) - Rasch, Elizabeth K.; Gulley, Stephen P.; Chan, Leighton
<x xml:space="preserve">Abstract</x> Objective To examine the relationship between emergency department (ED) use and access to medical care and prescription medications among working age Americans with disabilities. Data Source Pooled data from the 2006–2008 Medical Expenditure Panel Survey (MEPS), a U.S. health survey representative of community‐dwelling civilians. Study Design We compared the health and service utilization of two groups of people with disabilities to a contrast group without disability. We modeled ED visits on the basis of disability status, measures of health and health conditions, access to care, and sociodemographics. Data Extraction These variables were aggregated from the household component, the medical condition, and event files to provide average annual estimates for the period spanning 2006–2008. Principal Findings People with disabilities accounted for almost 40 percent of the annual visits made to U.S. EDs each year. Three key factors affect their ED use: access to regular medical care (including prescription medications), disability status, and the complexity of individuals' health profiles. Conclusions Given the volume of health conditions among people with disabilities, the ED will always play a role in their care. However, some ED visits could potentially be avoided if ongoing care were optimized.